Infrared spectrum analysis method for detection and early warning of longitudinal tear of mine conveyor belt. (1st December 2020) - Yang, Ruiyun; Qiao, Tiezhu; Pang, Yusong; Yang, Yi; Zhang, Haitao; Yan, Gaowei
Highlights: Monitor longitudinal tear with infrared thermography. Overcome the interference caused by the change of infrared image threshold. Select the appropriate detection spectral passband. Coefficient T can be used to quantitatively describe tear change characteristics. Abstract: A novel approach based on infrared spectrum analysis for early-warning of longitudinal tearing of the conveyor belt was proposed in the paper. Unlike most existing methods, the proposed method monitors the change process of the infrared radiation field of the longitudinal tearing through the infrared thermal imaging technology, and judges whether there is the risk of the longitudinal tearing of the conveyor belt through the frequency-domain characteristic coefficient T of the infrared radiation field. Experimental results exhibit that the characteristic coefficient T can quantitatively describe the change characteristics of infrared radiation field during the tearing process of conveyor belt. When the conveyor belt is complete penetration, the T value fluctuates violently from 0.6 to 1.6. This characteristic can be used as the precursor information of the tearing process, which broadens the train of thought for identification and early warning of conveyor belt longitudinal tearing.